2016
DOI: 10.1016/j.otsr.2016.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility analysis in adolescent idiopathic scoliosis on side-bending images using the EOS imaging system

Abstract: 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…13 EOS has also proven equivalent to conventional radiography in the evaluation of preoperative spinal flexibility. 15 Furthermore, in the 1 patient with a vagus nerve stimulator (VNS) in our study, EOS demonstrated excellent resolution of the hardware (Fig. 2).…”
Section: Discussionmentioning
confidence: 55%
“…13 EOS has also proven equivalent to conventional radiography in the evaluation of preoperative spinal flexibility. 15 Furthermore, in the 1 patient with a vagus nerve stimulator (VNS) in our study, EOS demonstrated excellent resolution of the hardware (Fig. 2).…”
Section: Discussionmentioning
confidence: 55%
“…Coupled axial rotation generally occurred in the same direction as lateral bending. The standing side-bending images of the EOS device contributed the same results as the supine images, with a five times lower radiation dose [21]. Nevertheless, none of these techniques were referred to specify the LIV.…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, for a three-dimensional assessment of scoliosis, biplanar radiographs are acquired when possible, since they allow 3D reconstruction of the bony structures [21,22]. It is possible that feeding radiographs with patients in different position (such as in lateral bending [23]) could alter the results. Nevertheless, the sample can be considered heterogeneous since the radiographs were acquired from five different hospitals in a time span of about 8 years.…”
Section: Discussionmentioning
confidence: 99%